Proceedings of the Workshop of the Stakeholder Consultation on Policy Coherence among Food, Land, and Water Systems in India, New Delhi, India, 16 June 2023 - Taneja, Garima; Katyaini, S.; Bhattacharjee, Suchiradipta; Chaturvedi, K.; Mitra, Archisman; Verma, Shilp; Bassi, N. (CGIAR Initiative on National Policies and Strategies, 2023)
Under the CGIAR Initiative on National Policies and Strategies (NPS), International Water Management Institute (IWMI) and Council for Energy, Environment, and Water (CEEW) jointly organized a National Stakeholder Workshop on “Policy Coherence for Food, Land, and Water” in India on 16th June 2023 at India Habitat Center in New Delhi. Guided by NITI Aayog, an apex public policy think tank of the Government of India, IWMI and CEEW researched the policy landscape at the national level in the food, land, and water (FLW) sectors, shortlisting seven central government schemes to understand ways to strengthen policy coherence and impact. The workshop was attended by representatives from the Ministry of Jal Shakti, the Ministry of Agriculture and Farmers’ Welfare, NITI Aayog and 17 government and civil society organizations working in the food, land, and water sectors. Under the able guidance of Debashree Mukherjee (Special Secretary, Ministry of Jal Shakti) and Avinash Mishra (Advisor, NITI Aayog), the participants discussed the study’s key recommendations, existing institutional mechanisms to catalyze coherence, harnessing synergies and balancing trade-offs across the food, land, and water sectors.